2010
DOI: 10.1177/003172171009100410
|View full text |Cite
|
Sign up to set email alerts
|

How Coaches Can Maximize Student Learning

Abstract: Heeding the roles and relationships of coaches enhances the likelihood that they will be able to influence school culture, professional learning, and, ultimately, student achievement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 0 publications
0
17
0
2
Order By: Relevance
“…A review of the literature revealed the qualities attributed to good coaches or supervisors fall into three categories: knowledge, disposition, and commitment (Borman & Feger, 2006;Obara, 2010;Saphier & West, 2010). The literature has also declared best practices for providing support to coaches (Charalambous, Philippou, & Kyriakides, 2008;Veenman & Denessen, 2001) and content specific coaching in the area of mathematics (Staub, et aI., 2003).…”
Section: Supervising Mathematicsmentioning
confidence: 99%
See 4 more Smart Citations
“…A review of the literature revealed the qualities attributed to good coaches or supervisors fall into three categories: knowledge, disposition, and commitment (Borman & Feger, 2006;Obara, 2010;Saphier & West, 2010). The literature has also declared best practices for providing support to coaches (Charalambous, Philippou, & Kyriakides, 2008;Veenman & Denessen, 2001) and content specific coaching in the area of mathematics (Staub, et aI., 2003).…”
Section: Supervising Mathematicsmentioning
confidence: 99%
“…Coaches work with adult learners in a situational context that differs from a classroom of students. Saphier and West (2010) define coaching as "a systematic approach to improving student learning" (p. 47). Sailors and Shanklin (2010) provide an expanded definition by stating, coaching is, "sustained classroom-based support from a qualified and knowledgeable individual who models research-based strategies and explores with teachers how to incorporate these practices using the teacher's own students" (p.1).…”
Section: Coaching and Mentoringmentioning
confidence: 99%
See 3 more Smart Citations